Expansion of the phosphatidylethanolamine binding protein family in legumes: a case study of Lupinus angustifolius L. FLOWERING LOCUS T homologs, LanFTc1 and LanFTc2. (December 2016) - Książkiewicz, Michał; Rychel, Sandra; Nelson, Matthew; Wyrwa, Katarzyna; Naganowska, Barbara; Wolko, Bogdan
Abstract Background TheArabidopsis FLOWERING LOCUS T (FT ) gene, a member of the phosphatidylethanolamine binding protein (PEBP) family, is a major controller of flowering in response to photoperiod, vernalization and light quality. In legumes, FT evolved into three, functionally diversified clades, FTa, FTb andFTc . A milestone achievement in narrow-leafed lupin (Lupinus angustifolius L.) domestication was the loss of vernalization responsiveness at theKu locus. Recently, one of two existingL. angustifolius homologs ofFTc, LanFTc1, was revealed to be the gene underlyingKu . It is the first recorded involvement of anFTc homologue in vernalization. The evolutionary basis of this phenomenon in lupin has not yet been deciphered. Results Bacterial artificial chromosome (BAC) clones carryingLanFTc1 andLanFTc2 genes were localized in different mitotic chromosomes and constituted sequence-specific landmarks for linkage groups NLL-10 and NLL-17. BAC-derived superscaffolds containingLanFTc genes revealed clear microsyntenic patterns to genome sequences of nine legume species. Superscaffold-1 carryingLanFTc1 aligned to regions encoding one or moreFT -like genes whereas superscaffold-2 mapped to a region lacking such a homolog. Comparative mapping of theL. angustifolius genome assembly anchored to linkage map localized superscaffold-1 in the middle of a 15 cM conserved, collinear region. In contrast, superscaffold-2 was found at the edge of a 20 cM syntenic block containing highly disrupted collinearity at theLanFTc2 locus. 118 PEBP-family full-length homologs were identified in 10 legume genomes. Bayesian phylogenetic inference provided novel evidence supporting the hypothesis that whole-genome and tandem duplications contributed to expansion of PEBP-family genes in legumes. Duplicated genes were subjected to strong purifying selection. Promoter analysis ofFT genes revealed no statistically significant sequence similarity between duplicated copies; only RE-alpha and CCAAT-box motifs were found at conserved positions and orientations. Conclusions Numerous lineage-specific duplications occurred during the evolution of legume PEBP-family genes. Whole-genome duplications resulted in the origin of subcladesFTa, FTb andFTc and in the multiplication ofFTa andFTb copy number.LanFTc1 is located in the region conserved among all main lineages of Papilionoideae.LanFTc1 is a direct descendant of ancestralFTc, whereasLanFTc2 appeared by subsequent duplication.